The diversity of free amino acids in 14 representative vietnamese rice accessions - To, Thi Mai Huong; Mai, Nga Thi Phuong (Academia Journal of Biology, 2025)
Rice (Oryza sativa L.) serves as the primary dietary staple for approximately half of the global population. Amino acids play a critical role in plant biology as they constitute the fundamental components of proteins. The free amino acid (FAA) content in rice holds nutritional significance due to its observable influence on the sensory qualities of cooked rice. In this study, 14 rice accessions from diverse ecosystems in Vietnam were selected for analysis of their FAA profiles to identify rice accessions possessing elevated levels of valuable FAA. High-performance liquid chromatography using the Biochrom 30+ system was employed for this purpose. The findings revealed substantial variability in FAA content among the rice accessions evaluated. Notably, the genotype G52 (BA TRANG HUONG) exhibited the highest concentration of FAA, indicating its potential utility as a genetic resource in breeding programs. Essential amino acids constituted approximately 36.1% of the total FAA content. Furthermore, significant differences in FAA, essential amino acids (EAA), and non-essential amino acids (NEAA) were observed between Indica and Japonica genotypes. Among the five amino acid families assessed, the glutamate and aspartate families demonstrated the highest concentrations. The outcomes of this study provide valuable insights that could inform future breeding efforts aimed at enhancing the FAA profile of rice varieties within the Vietnamese rice collection.